2014
DOI: 10.1089/jop.2014.0013
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular Proteins in the Trabecular Meshwork: Review and Update

Abstract: Primary open-angle glaucoma (POAG) is a leading cause of blindness worldwide, and intraocular pressure (IOP) is an important modifiable risk factor. IOP is a function of aqueous humor production and aqueous humor outflow, and it is thought that prolonged IOP elevation leads to optic nerve damage over time. Within the trabecular meshwork (TM), the eye's primary drainage system for aqueous humor, matricellular proteins generally allow cells to modulate their attachments with and alter the characteristics of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 269 publications
(245 reference statements)
0
38
1
Order By: Relevance
“…Naschberger et al showed that SPARCL1 contributes to tumor endothelial cell quiescence [61]. In POAG TM, Rhee and colleagues found that SPARC plays a role in IOP regulation and TM pathology [62]. Although we found a DEX-induced down-regulation of SPARCL1 in responders, it may indicate a remodeling of the TM.…”
Section: Discussioncontrasting
confidence: 52%
“…Naschberger et al showed that SPARCL1 contributes to tumor endothelial cell quiescence [61]. In POAG TM, Rhee and colleagues found that SPARC plays a role in IOP regulation and TM pathology [62]. Although we found a DEX-induced down-regulation of SPARCL1 in responders, it may indicate a remodeling of the TM.…”
Section: Discussioncontrasting
confidence: 52%
“…Mouse models targeting matricellular genes, including SPARC, thrombospondins-1 and −2, tenascins-C and –X, hevin and osteopontin, have been investigated (Chatterjee et al, 2014; Chowdhury et al, 2011; Haddadin et al, 2009; Haddadin et al, 2012; Kang et al, 2011; Keller et al, 2013). Of these, gene knockout of SPARC and both thrombospondins significantly lowered IOP in mice, while ablation of the other genes had minimal effects on IOP.…”
Section: Ecm Manipulations That Alter Iop In Animal Modelsmentioning
confidence: 99%
“…(Acott and Kelley, 2008; Vranka et al, 2015a, 2015b) For instance, the matricellular proteins shown altered in glaucoma specimens include SPARC, myocilin, CTGF, TSP-1, and -2. (Chatterjee et al, 2014) Changes in these and other proteins can be observed following treatment of cultured cells with stretching, dexamethasone, or TGF-beta stimuli. For example, increased expression of fibronectin, tenascin C, Versican, CD 44, syndecan, periostin, TSP-2, VCAM-1, GLA protein, and MMP-2 have been observed in response to stretch.…”
Section: Juxtacanalicular Tissue Cellsmentioning
confidence: 99%
“…Several details presented are striking such as origin, ultrastructural findings, cellular behaviors in culture and functional relationship with the surrounding ECM. They also are remarkably alike in terms of the type and protein components of their basement membrane and ECM, which are altered in glaucoma (Acott and Kelley, 2008; Chatterjee et al, 2014; Kirwan et al, 2009, 2005b, 2004; Liton et al, 2006; Rehnberg et al, 1987; Steely et al, 2000; Wallace and O’Brien, 2016). …”
Section: Similarities Between Lc and Jct Cells Related To Glaucomamentioning
confidence: 99%